Chlamydia screening in pregnancy in Australia: Integration of national guidelines into clinical practice and policy. (6th June 2013) - Li, Zhuoyang; Chen, Marcus; Guy, Rebecca; Wand, Handan; Oats, Jeremy; Sullivan, Elizabeth A.
Abstract : Background: Chlamydia trachomatis is the most common reportable infection in Australia. Since 2006, the Royal Australian and New Zealand College of Obstetricians and Gynaecologists (RANZCOG) have recommended chlamydia screening in pregnant women aged <25 years. Aims: To assess clinical uptake and policy integration of the 2006 RANZCOG recommendation on chlamydia testing in pregnant women aged <25 years. Methods: A mixed method approach was used involving a literature review, a survey of obstetricians and gynaecologists, and survey of hospital managers from April 2010 to May 2010. Results: Of the 1644 participating RANZCOG Fellows, Trainees, and Diplomates, 21.2% reported universal screening for pregnant women <25 years (25% of primary care clinicians, 23% of those working in the public hospital sector, 16% of those working in both public and private hospitals, and 13% of those in private hospitals or private practice). There was a strong association between members who agreed with the guideline and offering universal screening to pregnant women aged <25 years (adjusted odds ratio = 17.1, 95% CI: 6.0–49.2, P < 0.01). Of the 143 participating hospital managers who completed the hospital policy questionnaire; 20% reported that their hospital had a formal screening guideline. There were two national and four state/local policy documents recommending chlamydia screening in pregnancy. Conclusions: This study shows low uptake of chlamydia screening of young pregnant women by RANZCOG Fellows, Trainees, and Diplomates involved in antenatal care and highlights the need for national clinical leadership regarding screening for chlamydia among pregnant women aged <25 years.